2013
DOI: 10.2528/pier13042407
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Performance of Rice Husk-Carbon Nanotube Composites for Absorbing Microwave Signals in the Frequency Range of 12.4-18 GHZ

Abstract: Abstract-Composites of rice husks and carbon nanotubes (RHCNTs) are an innovation in improving the absorption of microwave signals. Rice husks, which are an agricultural waste material, have been found to possess a significant propensity for absorbing microwave signals. Studies have shown that both rice husks and carbon nanotubes (CNTs) have high percentages of carbon. Thus, in this paper, we present the results of our experimental study in which we varied the ratios of rice husks and CNTs in the composite mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Waste materials are getting considerable interest of researchers due to their good dielectric and magnetic properties, ease of availability, and low cost. [3][4][5][6][7][8] So far, less attention is given to the mineral dust and beach sand-based composite RAMs. In general, the effectiveness of the absorber mainly depends on the EM properties of the material (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Waste materials are getting considerable interest of researchers due to their good dielectric and magnetic properties, ease of availability, and low cost. [3][4][5][6][7][8] So far, less attention is given to the mineral dust and beach sand-based composite RAMs. In general, the effectiveness of the absorber mainly depends on the EM properties of the material (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…But, few have paid attention over waste composite material to be used for X-band frequency range especially for defence based applications. Recently, Lee et al [9] have studied the microwave absorption properties of rice husk-carbon nanotube (CNT) based composite material with varying percentages of CNTs. The rice husk-rubber tyre dust based composite material with enhanced microwave absorption over the frequency range of 7 to 13 GHz has been introduced by Cheng et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rice husks and other agricultural waste materials for example, have been found to possess a significant propensity for absorbing microwave signals. Previous studies have shown that this kind of agricultural wastes have high percentages of carbon [10][11][12]. Figure 1 The waveguide, the sample holder, the coir sample, and the polyurethane sample (left) and the total experimental setup (right).…”
Section: Introductionmentioning
confidence: 99%